Impact on Structural and Optical Properties of CZTS Thin Films with Solvents and Ge Incorporation - Abhay Kumar Singh; Tanka R. Rana; JunHo Kim; M. Shkir; Tien-Chien Jen (International Journal of Photoenergy)
This report demonstrates nontoxic colloidal nitrate route CZTS (Cu2ZnSnS4) synthesis at room temperature, along with their band grading due to incorporation of Ge as cost of Sn (3%). The parent CZTS, CZGTS (Cu2ZnGeSnS4), and their polyvinyl alcohol (PVA), dimethyl sulfoxide (DMSO) solvent containing solutions doctor blade-coated thin film structural and optical properties are discussed. Their sulfurized thin films thickness have been achieved ±2 μ. It has noticed that addition of Ge in CZTS alloy affects the grain sizes, crystallographic structure, Raman spectral peak shift toward the higher wave number side. The addition of PVA and DMSO is also substantially contributed in their physical property modification by demonstrating the gradual improvement in grain sizes and compactness. Moreover, the gradual changes have also appeared in their X-ray diffractometer (XRD) and Raman spectroscopic results. The optical energy band gaps of the CZTS, CZGTS, and their PVA, DMSO mixed alloyed thin films are obtained in between 1.27 eV to 1.57 eV and 1.58 eV to 1.83 eV.